2017
DOI: 10.1002/2017jc013383
|View full text |Cite
|
Sign up to set email alerts
|

A Lagrangian View of Spring Phytoplankton Blooms

Abstract: The mechanisms of spring phytoplankton blooms are investigated from a Lagrangian framework by using a Lagrangian NPZD model that can track the movement and transfers of nutrient parcels in a turbulent environment. The model reveals that the onset of spring blooms depends on the cumulative euphotic age, which is the total time that inorganic nutrient is exposed to light before the photosynthetic conversion to phytoplankton biomass. A spring bloom, defined as a tenfold increase of near‐surface phytoplankton, occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…These results, for p = 10 −6 or lower, bear a strong resemblance to the statistics of the BGC-Argo float observations in the Southern Ocean ( Figure 6 in Carranza et al, 2018), but suggest that, rather than by external forcing, chlorophyll variability is mostly caused by differences in the Lagrangian histories of water parcels (Kida and Ito, 2017;Baudry et al, 2018) but modulated by irreversible mixing. We remark that BGC-Argo floats are not high-resolution chlorophyll profilers (Carranza et al, 2018), and can't accurately represent vertical fluctuations on scales smaller than a few meters.…”
Section: Comparison With Bgc-argo Float Observationssupporting
confidence: 74%
See 1 more Smart Citation
“…These results, for p = 10 −6 or lower, bear a strong resemblance to the statistics of the BGC-Argo float observations in the Southern Ocean ( Figure 6 in Carranza et al, 2018), but suggest that, rather than by external forcing, chlorophyll variability is mostly caused by differences in the Lagrangian histories of water parcels (Kida and Ito, 2017;Baudry et al, 2018) but modulated by irreversible mixing. We remark that BGC-Argo floats are not high-resolution chlorophyll profilers (Carranza et al, 2018), and can't accurately represent vertical fluctuations on scales smaller than a few meters.…”
Section: Comparison With Bgc-argo Float Observationssupporting
confidence: 74%
“…Therefore, nearly all Lagrangian models (but see Dippner, 1998) neglect to include irreversible mixing processes. In the sporadic cases where Lagrangian and Eulerian formulations have been compared, this issue appears to have been overlooked (Wolf and Woods, 1988;Lande and Lewis, 1989;McGillicuddy, 1995;Kida and Ito, 2017;Baudry et al, 2018), even though it may lead to unrealistic, even paradoxical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows the PDF of τ r . Here τ r is calculated only during the daytime when μ = 1, and the euphotic zone is defined by the compensation depth ( z p = 23 m), as in Kida and Ito (2017). On a spring day of CON, τ r is divided into two groups of plankton; τ r = 0 h and τ r = 12 h. It is due to the fact that z p happens to be very close to h d in this case.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the CTH is applied when the mixed layer is deep and turbulence is weak, whereas the CDH is applied when the mixed layer is shallow and turbulence is strong (Huisman et al., 1999; Enriquez & Taylor, 2015; Kida & Ito, 2017; Taylor & Ferrari, 2011). Taylor and Ferrari (2011) proposed the condition K < ( μ m ) 2 / λ 2 m based on the CTH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation